Teacher education in Spain. The Bologne process - Barquín-Ruiz, Francisco Javier (My University, 2017)
It is a European Union-led process by which a European Higher Education Area has been created as a privileged means of promoting the mobility and employability of European citizens and the global development of the continent, recognising the role of universities in the enhancement of the European cultural dimension. The Bologna declaration of 1999, signed by 29 European ministers of education, marked the beginning of the process of convergence towards the EHEA which has become a reality in 2010. As a result of the implementation of the Bologna plan, the curriculum in the training of future teachers and Faculties of Education has been restructured . I will present a general description of the situation in terms of contents, credits, competences, specialities, characteristics of students, etc., within the general framework of the university in Spain. Teaching degree are the titles that have the greatest demand in the spanish universities.
Keywords: Profesores - Formación profesional; Educación - Estudio y enseñanza - Programas de estudio; Teacher Education; Bologne process; Curriculum Studies; Plan Study Faculty of Málaga